Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T16:21:13+01:00
A) (-4)+(-4)*(-2)-(-12) = -4+8+12 = 16
b) [8-8*(-4)-12*(-3)]*2 = [8+32+36]*2 = 76*2 = 152
c) (-34)+(-6)*[2-(-3)*4] = -40*[2+12] = -40*14 = -560
d) {4-[-(-6)*(-3)+3]-13}*(-4) = 4-[-18+3]-13*4 = 4+15-13*4 = 19-52 = -33
1 5 1
2010-01-19T16:21:41+01:00
A) (-4)+(-4)*(-2)-(-12)=-4+8+12=16
b) [8-8*(-4)-12*(-3)]*2=(8+32+36)*2 = 76*2 = 152
c) (-34)+(-6)*[2-(-3)*4]=-40*(2+12)=-40*14=-560
d) {4-[-(-6)*(-3)+3]-13}*(-4)=4-(-18+3(-13*4=4+15-13*4=19-52=-33
2010-01-19T18:03:19+01:00
A) (-4)+(-4)*(-2)-(-12)=-4+8+12=16
b) [8-8*(-4)-12*(-3)]*2=(8+32+36)*2 = 76*2 = 152
c) (-34)+(-6)*[2-(-3)*4]=-40*(2+12)=-40*14=-560
d) {4-[-(-6)*(-3)+3]-13}*(-4)=4-(-18+3(-13*4=4+15-13*4=19-52=-33